Práticas de sustentabilidade na construção civil: um estudo em empresas construtoras de edificações - (:unkn) unknown (Universidade Federal do Pampa, 2015)
In the last years, sustainability and sustainable development issues have grown in large proportion and awakened a progressive awareness in many sectors such as construction. The industrial construction of buildings is a great environment modifier and waste generating, since it is not a completely self-sustaining body. In order to improve the built environment and to minimize the impacts caused by the construction industry, valuation methodologies composed of sustainable practices have been created to measure the level of sustainability of a building. In the context presented, this study has as purpose to verify that the building construction companies are applying sustainable practices in their works from the application of a questionnaire to nine construction companies of buildings, located in countries such as Brazil, Spain, France and Italy. It was revealed that in Brazil there are already some sustainable solutions being used by the researched companies, for example: urban quality landscaping solutions, ventilation and natural lighting of bathrooms and common areas, use of prefabricated components, individual metering in buildings and RCD management. In European countries the reality is kind of different, since those companies adopt the most sustainable practices considered for the construction industry, especially those that relate to urban quality, energy efficiency, water management and pollution.
Keywords: Civil engineering; Construction; Sustainability; Buildings; Engenharia civil; Construção civil; Sustentabilidade; Edificações; CNPQ::ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL